NURSES’ SPIRITUAL WELL-BEING AND EXTENT OF PRACTICE OF SPIRITUAL CARE - Garcia, Albina L.; Martinez, Ma. Cecilia O. (LIFE: International Journal of Health and Life-Sciences, 2024)
This descriptive correlational study aimed to determine the level of awareness towards spiritual well-being and the extent of the practice of spiritual care of nurses who care for non-covid and COVID-19-infected adult patients at a tertiary hospital in Metro Manila. Data were gathered using two standardized questionnaires namely: The Spiritual Well-Being Scale (SWBS) created in 1982 by Craig W. Ellison and Raymond F. Paloutzian, and the Nurse Spiritual Care Therapeutics Scale (NSCTS) by Mamier and Tylor in 2015. Weighted Mean and Spearman’s Rho were used for the statistical treatment. Results of the study showed that the nurse respondents have a very high level of awareness towards spiritual well-being as to religious well-being (RWB) and existential well-being (EWB); they have a moderate extent of the practice in terms of spiritual care; there is a moderate significant relationship between the nurses’ level of awareness towards spiritual well-being in terms of religious well-being (RWB), existential well-being (EWB), overall spiritual well-being and their extent of practice of spiritual care. This implied that there is a relationship between the two variables accordingly but not to the highest degree; that is, the very high level of awareness towards spiritual well-being of nurses just moderately affected their extent of practice of spiritual care. Therefore, the researcher recommended more provision of spiritual care from the nurses for their patients.